Rantai Pasok Usaha Pembenihan Ikan Bandeng di CV Dewata Laut Desa Penyabangan, Kecamatan Gerokgak, Kabupaten Buleleng - Elfrida Sinafrin; Cening Kardi; I Made Budiasa (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
Milkfish hatchery business plays an important role in the aquaculture agribusiness system as it determines the sustainability of production at the grow-out stage. CV Dewata Laut, located in Penyabangan Village, Gerokgak District, Buleleng Regency, is a hatchery unit that supplies milkfish fry for domestic and export markets. However, the implementation of its supply chain system still faces challenges such as demand fluctuations, production risks, and distribution constraints. This study aims to identify the structure and main actors, as well as the supporting and inhibiting factors within the supply chain, and to analyze the flow of products, information, and finance in the milkfish hatchery business at CV Dewata Laut. This research employed a descriptive method with a qualitative approach and Supply Chain Flow Analysis. Data were collected through interviews, observations, and documentation. The analysis was conducted by identifying the supply chain structure, the roles of each actor, and the patterns of product, information, and financial flows based on actual field conditions. The results indicate that the supply chain structure consists of producers (CV Dewata Laut), collectors, and final consumers in domestic and export markets forming a simple vertical pattern. Product flows occur through direct and indirect channels, information flows in two directions, and financial flows are conducted through cash payments or agreed payment terms. Supporting factors include adequate production facilities and established customer networks, while inhibiting factors involve production risks, demand fluctuations, limited capital, and distribution constraints. Overall, the supply chain system functions adequately but requires improved coordination and risk management to achieve greater efficiency and sustainability.